2012
DOI: 10.1186/1753-2000-6-26
|View full text |Cite
|
Sign up to set email alerts
|

CHILDHOOD DEPRESSION. Exploring the association between family violence and other psychosocial factors in low-income Brazilian schoolchildren

Abstract: BackgroundChildhood depression affects the morbidity, mortality and life functions of children. Individual, family and environmental factors have been documented as psychosocial risk factors for childhood depression, especially family violence, which results in inadequate support, low family cohesion and poor communication. This study investigates the association between psychosocial depression factors in low-income schoolchildren and reveals the potential trouble spots, highlighting several forms of violence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 52 publications
0
23
1
1
Order By: Relevance
“…According to the studies selected, it can be concluded that depression in childhood is not simply a mood regulation disorder; it also involves alterations in the physiology and in the cognitive and social functions of children, and requires comprehension of developmental integration processes at multiple levels of biological, psychological, and social complexity in individuals [8,277].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…According to the studies selected, it can be concluded that depression in childhood is not simply a mood regulation disorder; it also involves alterations in the physiology and in the cognitive and social functions of children, and requires comprehension of developmental integration processes at multiple levels of biological, psychological, and social complexity in individuals [8,277].…”
Section: Resultsmentioning
confidence: 99%
“…Individual factors include age, gender, psychological and physical vulnerability [8,22], comorbidity with other disorders [8,23], emotional disturbance, impaired sociability, low self-esteem and social skill difficulties [8,24,25], according to Table 2 [8,22].…”
Section: Social and Environmental Factorsmentioning
confidence: 99%
See 3 more Smart Citations